EVALUATION OF THE ANTIOXIDANT ACTIVITY AND THE CYTOTOXICITY OF EXTRACTS OF CAPPARIS SPINOSA (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
The purpose of this study is to promote the plant spontaneous, harvested from the West of Morocco and streamline its use in quantifying the total phenolic content, assessing the antioxidant activity and testing the degree of toxicity on two types of eukaryotic cells plants and animals. The content, extracts aqueous and ethanolic flower buds and fruit, in phenolic compounds was determined according to the method Follin-Ciocalteu. The antioxidant activity was evaluated by two methods FRAP and DPPH. As for the cytotoxicity extracts, it has been evaluated by the test hemolysis and inhibition germination test of Lepidium sativum seeds. The different extracts of the two organs of this plant, have revealed richness in total polyphenols, especially those of the flower buds, as well as, an antioxidant activity, which is in the same order as that of vitamin C for the aqueous extract of flower buds. The effect hemolytic is shown positive for decoctat of flower buds. The ethanolic extract of fruits displayed an activity antimitotic expressed by the inhibition of elongation and growth seedlings of Lepedium sativum. The decoctat of flower exhibited an effect antigerminatif of moderate intensity which is reversible after rehydration of seed. Capparis Spinosa is a plant of quality pharmaceutical interesting for its activities antioxidant, antimitotic, healing, and for its wealth in phenolics compounds.